The Difference between Spouses in the Expiry of the Waiting Period and Its Impact on the Jordanian Personal Status Law No. (15) of 2019 - Tawalbeh, Afnan Yousef Ibrahim; Ananbeh, Sewar Ahmed Hussein (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study explores spousal disputes regarding the end of ʿiddah (waiting period after divorce or death), outlining the related legal rulings and juristic opinions. It examines claims by women that their ʿiddah ended—whether by menstruation, childbirth, or months—and whether the husband’s agreement or denial is legally valid. It also reviews the position of Jordanian Personal Status Law and related appellate decisions. Methods: The study adopts an inductive, analytical, and comparative approach. It traces jurisprudential issues concerning ʿiddah from the books of the Islamic legal schools, examines the relevant articles of the Jordanian Personal Status Law concerning ʿiddah and rajʿah (revocable divorce), presents case scenarios, analyzes and discusses the evidences, and weighs the different opinions according to the strength of the supporting proofs. Finally, it compares juristic views with the provisions of the Jordanian Personal Status Law. Results: The Jordanian Personal Status Law adopts the Hanafi position regarding disputes between spouses over the end of the ʿiddah. It states that a woman may observe ʿiddah due to menstruation, pregnancy, or months. If she is observing ʿiddah by menstruation or pregnancy and claims it has ended within a possible timeframe, her claim is accepted upon taking an oath. However, if she claims that her ʿiddah has ended by the passing of months, her claim is not accepted without evidence, and the husband’s oath is accepted. Conclusion: There is a pressing need for researchers to study jurisprudential disagreements related to marriage and divorce and their influence on legal choices in Arab and Jordanian personal status laws.